Museum XYZ, Major City, USA - Donnelly, Anne Cohn (London : SAGE Publications Ltd, 2017)
Museum XYZ built a beautiful facility in a large, Midwestern city. However, after opening to much acclaim, attendance began to fall off, finances were in a shambles, and there appeared to be a leadership void. The board hired two consultants to conduct a review to pinpoint the issues. This case discusses what the consultants learned, and the teaching note discusses what the board decided to do with the information.
Originally published: Cohn Donnelly, A. (2008). Museum XYZ, Major City, USA. (Revised in 15/04/2010). 5-208-256. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Museum attendance -- United States -- Evaluation -- Case studies; Museums -- Social aspects -- United States -- Case studies; Museums -- Public relations -- United States -- Case studies